Laminated Perovskite Photovoltaics: Enabling Novel Layer Combinations and Device Architectures. (9th January 2020) - Schmager, Raphael; Roger, Julie; Schwenzer, Jonas A.; Schackmar, Fabian; Abzieher, Tobias; Malekshahi Byranvand, Mahdi; Abdollahi Nejand, Bahram; Worgull, Matthias; Richards, Bryce S.; Paetzold, Ulrich W.
Abstract: High‐efficiency perovskite‐based solar cells can be fabricated via either solution‐processing or vacuum‐based thin‐film deposition. However, both approaches limit the choice of materials and the accessible device architectures, due to solvent incompatibilities or possible layer damage by vacuum techniques. To overcome these limitations, the lamination of two independently processed half‐stacks of the perovskite solar cell is presented in this work. By laminating the two half‐stacks at an elevated temperature (≈90 °C) and pressure (≈50 MPa), the polycrystalline perovskite thin‐film recrystallizes and the perovskite/charge transport layer (CTL) interface forms an intimate electrical contact. The laminated perovskite solar cells with tin oxide and nickel oxide as CTLs exhibit power conversion efficiencies of up to 14.6%. Moreover, they demonstrate long‐term and high‐temperature stability at temperatures of up to 80 °C. This freedom of design is expected to access both novel device architectures and pairs of CTLs that remain usually inaccessible. Abstract : The recent progress on laminated perovskite solar cells with power conversion efficiencies of up to 14.6% is demonstrated. The perovskite solar cells are processed by the lamination of two individually processed half‐stacks. This enables the possibility to access new device architectures and material combinations that are difficult or even impossible to process by conventional methods.